2011
DOI: 10.1089/ars.2010.3722
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cardioprotective Action of Adiponectin in High-Fat Diet–Induced Type II Diabetic Mice and Its Underlying Mechanisms

Abstract: Diabetes exacerbates ischemic heart disease morbidity and mortality via incompletely understood mechanisms. Although adiponectin (APN) reduces myocardial ischemia/reperfusion (MI/R) injury in nondiabetic animals, whether APN's cardioprotective actions are altered in diabetes, a pathologic condition with endogenously reduced APN, has never been investigated. High-fat diet (HD)-induced diabetic mice and normal diet (ND) controls were subjected to MI via coronary artery ligation, and given vehicle or APN globular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 30 publications
(42 reference statements)
4
71
0
Order By: Relevance
“…Furthermore, the finding that antioxidant treatment enhanced STAT3 activation in the heart of diabetic rats through APN signaling (9) suggests that malfunction of APN might be a key mechanism that rendered the diabetic heart less or not responsive to IPo cardioprotection. In addition, cardioprotective effects of APN were diminished in high-fat diet-induced diabetes (10,11), in which Cav3 is downregulated (12). This, together with our recent finding that Cav3 is disrupted (13) and STAT3 inactivated (9), which deranged eNOS signaling in diabetic myocardium with concomitantly reduced APN (9), indicates that APN signaling (e.g., AdipoR1/Cav3) is impaired in diabetes.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…Furthermore, the finding that antioxidant treatment enhanced STAT3 activation in the heart of diabetic rats through APN signaling (9) suggests that malfunction of APN might be a key mechanism that rendered the diabetic heart less or not responsive to IPo cardioprotection. In addition, cardioprotective effects of APN were diminished in high-fat diet-induced diabetes (10,11), in which Cav3 is downregulated (12). This, together with our recent finding that Cav3 is disrupted (13) and STAT3 inactivated (9), which deranged eNOS signaling in diabetic myocardium with concomitantly reduced APN (9), indicates that APN signaling (e.g., AdipoR1/Cav3) is impaired in diabetes.…”
mentioning
confidence: 54%
“…In addition to type 1 diabetes, IPo cardioprotective effects were also reduced in type 2 diabetes (44), and we have shown that APN cardioprotective effects also reduced in type 2 diabetes associated with reduced APN content (10,11). However, whether IPo can increase the interaction of AdipoR1 and Cav3 in type 2 diabetes is not known.…”
Section: Discussionmentioning
confidence: 96%
“…97 However, in dissimilar fashion to APN-deficient mice (which lack phenotypic changes under physiologic conditions), CTRP9-deficient mice are obese, insulin resistant, and exhibit hepatic steatosis with reduced skeletal muscle AMPK activation and mitochondrial content. 84 Such results are genetic evidence for a physiologic role of CTRP9, suggesting that CTRP9 may play a significant role in cardiovascular homeostasis. Additionally, CTRP9 primarily circulates in the plasma as the gCTRP9 isoform.…”
Section: Ctrp9mentioning
confidence: 84%
“…This is different tective effect of APN. 84 As mentioned before, the efficacy of recombinant exogenous APN in ameliorating myocardial I/R disease has been demonstrated in multiple animal studies. The practical clinical application of exogenous recombinant APN is limited for multiple reasons such as APN's complex quaternary structure, rapid turnover, and the high cost of pro- Figure 4.…”
Section: Ctrp9mentioning
confidence: 86%
See 1 more Smart Citation